How Christian Is Christian Education? The Relation of Theology and Education in the Church - Estep, James Riley (Stone-Campbell journal, 2006)
As Christian educators ponder the future direction of Christian education, one critical question is the degree to which theology influences the form and substance of education that is Christian. The theological base of education has become an assumption within the Christian community, serving as a foundation, framework, or core of education that is Christian. However, the degree of theological influence varies between Christian educators. This study advocates a high level of integration between theology and education and itemizes the benefits for Christian education and educators in the church.